A CD8α− Subset of CD4+SLAMF7+ Cytotoxic T Cells Is Expanded in Patients With IgG4‐Related Disease and Decreases Following Glucocorticoid Treatment - Della‐Torre, Emanuel; Bozzalla‐Cassione, Emanuele; Sciorati, Clara; Ruggiero, Eliana; Lanzillotta, Marco; Bonfiglio, Silvia; Mattoo, Hamid; Perugino, Cory A.; Bozzolo, Enrica; Rovati, Lucrezia; Arcidiacono, Paolo Giorgio; Balzano, Gianpaolo; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2018)
Objective An unconventional population of CD4+ signaling lymphocytic activation molecule family member 7–positive (SLAMF7+) cytotoxic effector memory T (TEM) cells (CD4+ cytotoxic T lymphocytes [CTLs]) has been linked causally to IgG4‐related disease (IgG4‐RD). Glucocorticoids represent the first‐line therapeutic approach in patients with IgG4‐RD, but their mechanism of action in this specific condition remains unknown. We undertook this study to determine the impact of glucocorticoids on CD4+ CTLs in IgG4‐RD. Methods Expression of CD8α, granzyme A, perforin, and SLAMF7 within the effector memory compartment of CD45RO+ (TEM) and CD45RA+ effector memory T (TEMRA) CD4+ cells was quantified by flow cytometry in 18 patients with active IgG4‐RD, both at baseline and after 6 months of glucocorticoid treatment. Eighteen healthy subjects were studied as controls. Next‐generation sequencing of the T cell receptor α‐ and β‐chain gene was performed on circulating CD4+ CTLs from patients with IgG4‐RD before and after treatment and in affected tissues. Results Circulating CD4+ TEM and TEMRA cells were not expanded in IgG4‐RD patients compared to healthy controls. CD4+SLAMF7+ TEM cells (but not TEMRA cells) were significantly increased among IgG4‐RD patients. Within CD4+SLAMF7+ TEM cells, CD8α− cells but not CD8αlow cells were elevated in IgG4‐RD patients. The same dominant clones of CD8α−CD4+SLAMF7+ TEM cells found in peripheral blood were also identified in affected tissue. CD8α− and CD8αlowCD4+SLAMF7+ TEM cells both expressed cytolytic molecules. Clonally expanded CD8α− but not CD8αlowCD4+SLAMF7+ TEM cells decreased following glucocorticoid‐induced disease remission. Conclusion A subset of CD8α−CD4+SLAMF7+ cytotoxic TEM cells is oligoclonally expanded in patients with active IgG4‐RD. This TEM cell population contracts following glucocorticoid‐induced remission. Further characterization of this cell population may provide prognostic information and targets for therapeutic intervention.